Effect of The Thai traditional plant formula, hing-hai on colon cancer cell growth and metastasis - Rujirek Chaiwongsa (2018)
© 2018, Chiang Mai University. All rights reserved. A Thai traditional formula named Hing-Hai is a water extracted mixtures of 7 particular medicinal plants. It is well-known and prescribed to treat 3 major cancers including colon, liver and lung. However, there was no scientific support for its effect and its detailed mechanism remained elusive. This work aimed to evaluate the anti-cancer effect of Hing-Hai and explore its mechanism of action. Hing-Hai was cytotoxic to Caco2 and SW620 in dose-dependent with IC50of 234 and 438 μg/ml, respectively by MTT assay. Assay on apoptotic induction and cell cycle analysis using flow cytometry revealed that Hing-Hai did not induce apoptosis or arrest the cell cycle. Studies of cell adhesion in the presence of 3 major adhesion molecules including collagen I, fibronectin, and vitronectin, demonstrated that Hing-Hai inhibited adhesion of both cancer cells in dose-dependent manner. Scratch wound-healing motility assay and gelatin zymography also confirmed that Hing-Hai could delay cell migration and decrease gelatinolytic activity. Interestingly, at the same concentration, Hing-Hai effectively inhibited adhesion, migration, and decreased the gelatinolytic activity of SW620 more than that of Caco2 cell. These findings support anti-colon cancer activity of Thai traditional plant formula, Hing-Hai. The studies clearly confirmed anti-cancer activity based on the inhibition of cell adhesion and migration and decreasing the elatinolytic activity.